A mesoscale framework for analysis of corrosion induced damage of concrete. (20th August 2019) - Seetharam, S.C.; Laloy, E.; Jivkov, A.; Yu, L.; Phung, Q.T.; Pham, N.P.; Kursten, B.; Druyts, F.
Highlights: Mesoscale model integrating gradient-based damage with cohesive zones. Model parameters obtained by global optimization of three-point bending tests. Corrosion-induced damage of large concrete containers investigated. Damage evolution found strongly dependent on outer boundary condition. Important implications for design and storage of waste containers discussed. Abstract: A mesoscale damage framework is developed for investigating the extent of crack or damage penetration in a large-scale concrete component induced by corrosion process under various boundary conditions. The framework synthesizes a robust particle generation algorithm, a state of the art mesoscale damage model and a global optimization algorithm. Three-point bending experiments on geometrically similar specimens, designed to capture the size effect reasonably well, are reported and used as the basis for estimating mesoscale damage parameters. The results show how boundary conditions control damage evolution, realizing scenarios from complete penetration to arrest of damage at different penetration levels within the component. In particular, it is shown that damage is arrested under external pressure and fixed displacement boundary conditions, but fully penetrates under stress-free boundary condition. The outcome is significant for the integrity assessment of concrete elements encapsulating corroding metallic containers.